2014
DOI: 10.1007/s12672-014-0198-6
|View full text |Cite
|
Sign up to set email alerts
|

FASNating Targets of Metformin in Breast Cancer Stem-Like Cells

Abstract: Diabetes, Breast Cancer, and MetforminEmerging data suggest that metformin treatment is associated with reduced breast cancer incidence and mortality for individuals with type II diabetes [7,6,17]. For years, many studies have been done to investigate the possible direct and indirect effects of metformin on cancers of various origins. In diabetic patients, metformin improves metabolic function by promoting muscle glucose uptake and lowering hepatic gluconeogenesis [14,15,36]. In cultured cancer and normal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…We also observed the phosphorylation of ACC in response to AICAR at concentrations used in this study. Furthermore, metformin decreased FASN protein levels in breast cancer cells [49] and the FASN inhibitor orlistat up-regulated AMPK activity in lung cancer cells [50]. This demonstrates the critical role of fatty acid metabolism in cellular energy production and suggests an important interaction between AMPK and FASN.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed the phosphorylation of ACC in response to AICAR at concentrations used in this study. Furthermore, metformin decreased FASN protein levels in breast cancer cells [49] and the FASN inhibitor orlistat up-regulated AMPK activity in lung cancer cells [50]. This demonstrates the critical role of fatty acid metabolism in cellular energy production and suggests an important interaction between AMPK and FASN.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that FASN expression positively correlates to cancer stages, including prostate cancer [ 8 ], renal cancer [ 9 ], and colorectal cancer [ 10 ]. Moreover, FASN inhibition can decrease the cancer cell stemness in breast cancer [ 11 , 12 ] and glioma [ 13 ]. Interestingly, it has been shown that sorafenib-resistant HCC cells demonstrate more characteristics of cancer stem cells than their parental counterparts [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%